Persepsi Masyarakat terhadap Implementasi Kebijakan Zonasi Pasar Modern di Kabupaten Sidoarjo - Isnaini Rodiyah; Ilmi Usrotin Choiriyah (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2015)
This study aimed to describe the results of public perception of the policy implementation on modern market zoning. This type of research used qualitative research through the explanation method. Data was collected through interviews with employees of the modern market and government officials in Sidoarjo Regency as the basis of the policy implementation; in addition it is also supported by literature study related to the zoning policy of the modern market. The results showed that the modern market employees and government officials agree associated with modern market competition that is unhealthy and affect traditional markets. In addition, it was found that the licensing process was not in accordance with the procedure. It can be concluded, based on public perception stated that three main factors that affect of policy implementation zoning the modern market, namely the lack of effective communication between the government and the owners of the modern market; abuse of licensing and lack of socialization of the modern market zoning.